FOXO3a-BAP1 axis regulates neuronal ferroptosis in early brain injury after subarachnoid hemorrhage - Chengli Liu; Qi Tian; Zhijie Li; Guijun Wang; Wenrui Han; Shengming Jiang; Zhou Sun; Qingqing Xu; Long Wang; Jianming Liao; Mingchang Li (Redox Biology)
Subarachnoid hemorrhage (SAH) is a serious and common disease and accounts for about 10 % of acute stroke cases. BRCA-associated protein 1 (BAP1) belongs to the ubiquitin C-terminal hydrolases (UCHs) family, which plays an important role in cell metabolism and cell death, but its role in early brain injury (EBI) after SAH requires further study. Forkhead box protein O3a (FOXO3a) is a transcription factor involved in the regulation of cellular function and survival in the nervous system, including the oxidative stress response and neuronal death. This study aimed to explore the effect of FOXO3a and BAP1 on neuronal ferroptosis in the pathogenesis of EBI after SAH. In this study, the overexpression of BAP1 significantly inhibited GPX4 expression and exacerbated the degree of lipid peroxidation and ferroptosis in neurons after SAH. BAP1 regulated the transcription level of the SLC7A11 promoter by H2Aub. FOXO3a could transcriptionally regulate BAP1 to influence the levels of SLC7A11 and GPX4, and mediate lipid peroxidation and neuronal ferroptosis after SAH. Silencing FOXO3 and BAP1 significantly improved neurological deficit and cerebral edema, and reduced oxidative stress damage in SAH mice. After SAH, BAP1 could directly bind to the FKH-DBD + NLS domain located in FOXO3a protein through the UCH domain, and mediates deubiquitination of FOXO3a protein by the K48 site to maintain the stability of FOXO3a. Our findings elucidate the impact of FOXO3a and BAP1 on SLC7A11-related ferroptosis following SAH both in vivo and in vitro, and the inhibition of the FOXO3a-BAP1 axis can significantly attenuate neuronal damage and ferroptosis in EBI after SAH.